Addressing Child Sexual Abuse: A Call to Action for Providers in Latin America - Casas-Muñoz, Abigail (2023)
The objective of this communication is to outline the key elements required to train health care providers in various occupations (medicine, psychology, dentistry, nursing, social work, nutrition, physiotherapy, occupational therapy, chemistry, pharmacy, and obstetrics, including midwifery, among others) to address child sexual abuse (CSA) and develop care protocols grounded on evidence-based practices, as well as provide resources to optimize both processes. Training on child and adolescent sexual abuse is an essential component of facing this major challenge in Latin America and allowing health care personnel to fulfill their role of safeguarding the security and well-being of children and adolescents. Developing protocols helps health care staff define the roles and responsibilities of individual members, summarize potential red flags of CSA, and describe strategies to best identify and address the health and safety needs of patients and their families, which should include a trauma-informed approach. Future work should focus on developing and evaluating new strategies to increase the capacity of the health sector to care for children experiencing CSA and optimizing ways to train staff. Further aims should also include improving research and evidence generation on the epidemiology and care of CSA in Latin America, including of male children and adolescents, minorities, and priority groups (e.g., migrant children, children with disabilities, street children, youth deprived of liberty, indigenous communities and the LGBTQI+ community).